2017
DOI: 10.21873/anticanres.12105
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and Long-term Results of Radiofrequency Ablation for Colorectal Liver Metastases

Abstract: RFA of CRLMs is a safe procedure with low rates of local relapses and recurrences, as well as acceptable survival rates, in the first 24-36 months post-procedure. It is recommended for patients with no indications for liver resection or having major resection risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
4
1
Order By: Relevance
“…8 As reported previously, we revealed that patients with tumor sizes larger than 3 cm had a poor prognosis. [29][30][31] However, another prognostic factor, the number of liver tumors, was not an independent predictor of survival in this study. This discrepancy may have been due to the relatively lower lesion-topatient ratio (1.56, 125/80) in this study.…”
Section: Discussioncontrasting
confidence: 74%
“…8 As reported previously, we revealed that patients with tumor sizes larger than 3 cm had a poor prognosis. [29][30][31] However, another prognostic factor, the number of liver tumors, was not an independent predictor of survival in this study. This discrepancy may have been due to the relatively lower lesion-topatient ratio (1.56, 125/80) in this study.…”
Section: Discussioncontrasting
confidence: 74%
“…Almost 30 years have passed since the introduction of RFA, and data have been accumulated steadily regarding CRC liver metastasis and not only hepatocellular carcinoma, which is in high demand for RFA. Cirimbei reported in a retrospective study regarding immediate and long-term results of RFA for unresectable or non-operable liver metastasis of CRC, and indicated that RFA is safe, has low rates of local relapses and recurrences, and acceptable survival rates (23). As a minimally invasive local treatment, the main roles of RFA for unresectable or non-operable cases of CRC with liver metastasis are to assist as a complementary local treatment and to control liver metastases in cases with a defined prognosis due to liver metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant tumors have an abundant blood supply and large number of AV fistula structures, making it easy to relapse or even accelerate the treatment progress. In recent years, ablation therapy has been used in the clinical treatment of a variety of malignant tumors, and the method has achieved good results [ 25 ]. Inspired by these findings, we applied this technique to cases of complex AV malformations in which other methods had failed many times; the process was conducted in December 2014 after multidisciplinary consultation.…”
Section: Discussionmentioning
confidence: 99%